2016
DOI: 10.1093/abbs/gmv102
|View full text |Cite
|
Sign up to set email alerts
|

The greedy nature of mutant RAS: a boon for drug discovery targeting cancer metabolism?

Abstract: RAS oncogene mutations are frequently detected in human cancers. Among RAS-mediated tumorigenesis, KRAS-driven cancers are the most frequently diagnosed and resistant to current therapies. Despite more than three decades of intensive efforts, there are still no specific therapies for mutant RAS proteins. While trying to block those well-established downstream pathways, such as the RAF-MAPK pathway and the PI3K-AKT pathway, attentions have been paid to potential effects of RAS on metabolic pathways and the feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 148 publications
0
9
0
Order By: Relevance
“…The pronounced effect of NRAS mutations on survival, particularly in combination with TERT promoter mutations, can probably be attributed to its involvement in multiple pathways. Besides being upstream of the RAF–MAPK pathway, RAS also affects metabolic pathways and promotes aerobic glycolysis and glutamine metabolism to provide energy and facilitate autophagy and macropinocytosis, which generate building blocks for tumour growth and strengthen the antioxidant defence in tumour cells 17,31 . However, due to the dependence of TERT expression on RAS signalling in mutant tumours, targeting with the telomere‐uncapping agent 6‐thio‐2′‐deoxyguanosine in combination with the mitochondrial inhibitor gamitrinib has been shown to suppress NRAS ‐mutant melanoma effectively in cells and animal models 32 …”
Section: Discussionmentioning
confidence: 99%
“…The pronounced effect of NRAS mutations on survival, particularly in combination with TERT promoter mutations, can probably be attributed to its involvement in multiple pathways. Besides being upstream of the RAF–MAPK pathway, RAS also affects metabolic pathways and promotes aerobic glycolysis and glutamine metabolism to provide energy and facilitate autophagy and macropinocytosis, which generate building blocks for tumour growth and strengthen the antioxidant defence in tumour cells 17,31 . However, due to the dependence of TERT expression on RAS signalling in mutant tumours, targeting with the telomere‐uncapping agent 6‐thio‐2′‐deoxyguanosine in combination with the mitochondrial inhibitor gamitrinib has been shown to suppress NRAS ‐mutant melanoma effectively in cells and animal models 32 …”
Section: Discussionmentioning
confidence: 99%
“…KRAS mutations are frequently associated with a metabolic reprogramming, such as highly active glucose metabolism, differential channeling of glucose intermediates, reprogrammed glutamine metabolism, and increased autophagy and macropinocytosis (4,14). These changes are critical for utilization of nutrients to satisfy biosynthetic demands and maintain redox equilibrium for cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous findings demonstrate the involvement of mutant KRAS in the metabolic rewiring of several types of human cancer ( Pylayeva-Gupta et al ., 2011 ; Kimmelman, 2015 ; Lv et al ., 2016 ; Kawada et al ., 2017 ; Kerr and Martins, 2017 ), including upregulation of glucose uptake, glutamine utilization, and aerobic glycolysis ( Onetti et al ., 1997 ; Ying et al ., 2012 ; Son et al ., 2013 ). Using patient-derived NSCLC tumors, cell lines, and animal models, several studies have consistently identified the influence of mutant KRAS on metabolic reprogramming in NSCLC.…”
Section: Role Of Oncogenic Mutations In Metabolic Reprogramming In Lumentioning
confidence: 99%